Subpopulations of cells from bronchoalveolar lavage can predict prognosis in sarcoidosis. Issue 1 (30th January 2020) - Darlington, Pernilla; Kullberg, Susanna; Eklund, Anders; Grunewald, Johan
Sarcoidosis is characterised by an accumulation of CD4 + T-cells in the lungs and an increased bronchoalveolar lavage fluid (BALF) CD4/CD8 ratio (>3.5) [1]. In sarcoidosis, an expansion of BALF CD4 + T-cells expressing the T-cell receptor Vα2.3 has been associated with good prognosis and with specific HLA-alleles, i.e. HLA-DRB1*0301 and HLA-DRB3*0101 (which is often carried together with HLA-DRB1*13). HLA-DRB1*03 and HLA-DRB3*0101 molecules show similarities in the region important for antigen presentation and both may therefore be capable of presenting identical antigens to the lung T-cells [2]. The higher the proportion of a T-cell subset (CD4 + Vα2.3 + T-cells) in bronchoalveolar lavage fluid of sarcoidosis patients, the better the prognosis and therefore it may be used as an additional prognostic tool http://bit.ly/2Mta0Cs